Governing America : an introduction - Sherrill, Robert (New York : Harcourt Brace Jovanovich, 1978)
Examines political processes and issues that affect the future of every United States citizen.
Includes bibliographical references and index.
Keywords: United States -- Politics and government -- Handbooks, manuals, etc; United States -- Politics and government